2023
DOI: 10.1029/2022jd038103
|View full text |Cite
|
Sign up to set email alerts
|

Last Glacial Maximum ITCZ Changes From PMIP3/4 Simulations

Abstract: The intertropical convergence zone (ITCZ) is the region near the equator where the trade winds of the Northern and Southern Hemispheres converge. It appears as a band of heavy precipitation that encircles the globe. The annual precipitation in the ITCZ accounts for 32% of the globally integrated precipitation in the current climate (Kang et al., 2018). The ITCZ has an important impact on the Earth's climate. In the tropics, the ITCZ modulates cyclone genesis and the convective initiation of the Madden-Julian O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
0
3
2
Order By: Relevance
“…Using the present-day geochemically defined mean ITCZ position of 6°N-7°N as a reference, it is concluded that the annual mean ITCZ position was about 3°s outh during the LGM and 1°-3°south during HS1 relative to the present (Figure 2). The maximum 3°latitudinal shift observed in this study is much larger than the global average of <1°southward shift during the LGM and HS1 estimated by models and paleoclimate reconstructions (Atwood et al, 2020;McGee et al, 2014;Wang et al, 2023). However, these studies pointed out potential greater shift of the precipitation centroid in the central Pacific.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Using the present-day geochemically defined mean ITCZ position of 6°N-7°N as a reference, it is concluded that the annual mean ITCZ position was about 3°s outh during the LGM and 1°-3°south during HS1 relative to the present (Figure 2). The maximum 3°latitudinal shift observed in this study is much larger than the global average of <1°southward shift during the LGM and HS1 estimated by models and paleoclimate reconstructions (Atwood et al, 2020;McGee et al, 2014;Wang et al, 2023). However, these studies pointed out potential greater shift of the precipitation centroid in the central Pacific.…”
Section: Discussioncontrasting
confidence: 83%
“…The maximum 3° latitudinal shift observed in this study is much larger than the global average of <1° southward shift during the LGM and HS1 estimated by models and paleoclimate reconstructions (Atwood et al., 2020; McGee et al., 2014; Wang et al., 2023). However, these studies pointed out potential greater shift of the precipitation centroid in the central Pacific.…”
Section: Discussioncontrasting
confidence: 61%
“…Climate model simulations of the Heinrich stadials show decreased northward OHT and an associated equatorward shift of the ITCZ, weakening of the NH monsoons, and a relatively wetter climate in the SH 236 . Similar to other cold periods, reconstructions for the last glacial maximum show a southward shift of the ITCZ 233 and reinforced northeast trade winds 105, 237 . Trade winds proxies of the HC during cold episodes are consistent with the response predicted in the section “Linking the ITCZ position with ocean heat transport, TOA flux, and SST”: cooling the NH relative to the SH shifts the ITCZ equatorward and strengthens the NH trade winds, while it weakens them in the SH 236 .…”
Section: The Responses Of the Hc To Natural And Anthropogenic Forcingsmentioning
confidence: 80%
“…PMIP simulations of LGM ($\sim$21 kyr BP) clearly show that the winter solstitial HC was stronger and narrower than in preindustrial conditions 105, 108 . Literature also provides a consensus on a equatorward shift of the ITCZ 233 . During the glacials and cold episodes, such as the Younger Dryas (12.9–11.7 kyr BP) and Heinrich stadials, the complex interplay between orbital and CO 2 forcing, and ice‐sheets dynamics presumably led to an AMOC slowdown 234, 235 .…”
Section: The Responses Of the Hc To Natural And Anthropogenic Forcingsmentioning
confidence: 97%
“…The data set employed in this research is sourced from the Paleoclimate Modeling Intercomparison Project Phase III and Phase IV (Braconnot et al., 2011; Kageyama et al., 2021; T. Wang et al., 2023, PMIP3/PMIP4) LGM experiment and Pre‐industrial (PI) control run. A total of nine models from PMIP3 and five models from PMIP4 were included in our investigation.…”
Section: Methodsmentioning
confidence: 99%